Outbreak of novel Corona virus (2019-nCoV); implications for travelers to Pakistan - Qureshi, Ubaid Ur Rahman; Saleem, Sadia; Khan, Aisha; Afzal, Muhammad Sohail; Ali, Muhammad Shahzad; Ahmed, Haroon (Elsevier Sci Ltd, 2020)
[Abstract Not Available]